EFFECT OF WEIGHT OF REINFORCEMENT AND COATING THICKNESS ON THE HARDNESS OF STIR CAST AL7075-NICKEL COATED DURALUMIN POWDER MMC - B M, Karthik; Sharma, Sathyashankara; M C, Gowrishankar; Hegde, Ananda; Srinivas, Doddapaneni (Journal of Applied Engineering Science, 2022)
In the present work, it is experimented to reinforce duralumin powder (3 to 7 wt %.) into Al7075 matrix by stir casting technique. Since matrix and reinforcement both have almost similar melting temperatures, the least expensive additive manufacturing metallurgical route seems to be the best fit. In this study, an effort was made to produce the Al7075 matrix composite reinforced with duralumin by a novel stir casting method by coating duralumin powders with nickel which has high temperature melting point compared to reinforcement material.. Nickel has good wettability and avoids undesirable chemical reactions between the reinforcement and matrix at higher temperatures, acting as a protector for both the duralumin and matrix. Since, aging kinetics of duralumin (Al2024) and Al7075 are different, both positively respond to heat treatment in a single stretch for property alteration. During stir casting, even though duralumin melts along with the matrix, it will be under the solid protection barrier (coat) of nickel, avoiding dissolution with the Al7075 matrix. To verify the presence of reinforcement duralumin in the matrix and to decide the soundness of the casting produced by stir casting, confirmation tests are made like microstructures with EDS and microhardness distribution. The microstructure analysis of the composite showed an even distribution of nickel coated duralumin in the matrix when the coating thickness of a nickel is greater than 8 µm. The hardness test analysis has shown an improvement in the hardness with the increase in the weight % of the reinforcement. Improvement in the hardness of composites is due to an increase in dislocation number, which shows higher resistance to plastic deformation [2]. Statistical analysis has shown that the coating of reinforcement does not have any significant effect on the mechanical properties. The regression equation is fit to determine the hardness of the composite involving the factors within the range of values considered for this study.
Keywords: stir cast, coating, composites